If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-1x+1(x-1)=2
We move all terms to the left:
-1x+1(x-1)-(2)=0
We move all terms containing x to the left, all other terms to the right
-1x+1(x-1)=2
| 60=2/3x+x | | 5(x-9)=35-3x | | (3x+33)(2x-3)=180 | | 3(w-5)-8w=5 | | 0.5(6x-4)=3x+2 | | 2(2x)+x=17.5 | | 1(x-1)=x+2 | | (3x–1=-10) | | -8x+83=-x-176 | | 11b+20=40 | | 12+4n=–4 | | -30-5x=123 | | (x-5)2=x+1 | | -12m+4m=18-3 | | c÷2=14 | | (x-5)^2=x+1 | | 8x-5=8(x-7) | | (x-5)²=x+1 | | 18y-6=3(6y-2) | | 1=-8y^2 | | u=-4u^2 | | n/10=9=17 | | 5x+4=9x=12 | | 9p=-7p^2-1 | | 20=8+2r | | 20=8+2e | | 1=-2v^2-2v | | 1.73=200x-20 | | 2v^2-7=0 | | 4q^2=-3 | | -25=-5(x+5) | | 24.5-x-2=3+4x+5 |